Theoretical and historical issues of the civil society research as political and legal phenomenon - Turlayev, A.V.; Poleva, I.A.; Tuyakova, N.B. (KU Publ., 2021)
The article reveals the theoretical and historical issues of identifying civil society and its main features. The dynamic nature of this political and legal phenomenon, associated in the law theory and state with the law, has been identified. The experience of researching civil society in different historical periods under historical retrospective, the variability and development of this institution in the theories and various authors’ approaches have been considered. The research purpose is to point out the civil society’s main features by revealing its main functions. Using general and special research methods, the analysis and generalization of historical and theoretical material, political and legal acts, which define the concept and civil society features, were carried out. The concept and features of the civil society definition were determined while civil control was considered as the main and defining civil society feature in the relationship between civil society and the law rule. Civil society is viewed as a political and legal category that requires legal regulation of these relationships. As a result, the authors of the article conclude that civil control and civil monitoring are the main civil society features in relations with the legal state. These relationships require more detailed legal regulation and legal status of civil society determination of the institutions that exercise civil control and civil monitoring.
Саяси-құқықтық құбылыс ретінде азаматтық қоғамды зерттеудің теориялық және тарихи мәселелері
Теоретико-исторические проблемы исследования гражданского общества как политико-правового явления
Keywords: civil society; civil institutions; legal state; legal norms; historical development; theory of law